2011
DOI: 10.1242/jcs.086686
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of GSK-3β activation by M-cadherin protects myoblasts against mitochondria-associated apoptosis during myogenic differentiation

Abstract: Apoptosis occurs concurrently with differentiation of muscle progenitor cells (MPCs) before they fuse to form myotubes. Dysregulated apoptosis in MPCs contributes to the low regeneration capability in aged muscle and decreases the survival rate of donor cells in stem cell-based therapies for muscular dystrophies. This study investigated the role of the M-cadherin/PI3K/Akt/GSK-3β signaling pathway in regulating apoptosis during differentiation of MPCs. Disruption of M-cadherin-dependent cell-cell adhesion by M-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…In contrast, a study designed to investigate the mitochondrial dysfunction during fasting concluded it was a consequence rather than a cause of insulin resistance (Hoeks et al, 2010). Indeed, when associated with cell death or apoptosis, mitochondrial dysfunction is reported to occur after GSK-3␤ activation (Petit-Paitel et al, 2009;Wang et al, 2011), placing it after insulin resistance (Fig. 1).…”
Section: Tumor Necrosis Factor and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…In contrast, a study designed to investigate the mitochondrial dysfunction during fasting concluded it was a consequence rather than a cause of insulin resistance (Hoeks et al, 2010). Indeed, when associated with cell death or apoptosis, mitochondrial dysfunction is reported to occur after GSK-3␤ activation (Petit-Paitel et al, 2009;Wang et al, 2011), placing it after insulin resistance (Fig. 1).…”
Section: Tumor Necrosis Factor and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…However, there is evidence that apoptotic signaling in myonuclei and satellite cells may have a role in regulating muscle loss in response to forced disuse (Alway et al, 2014a; Alway et al, 2015; Alway et al, 2011; Alway et al, 2014b; Hao et al, 2011; Marzetti et al, 2013a; Marzetti et al, 2012; Wang et al, 2011). Loss of autophagy signaling in satellite cells/muscle stem cells in aging muscle (Garcia-Prat et al, 2016; Sousa-Victor et al, 2014) might increase the susceptibility of satellite cells for apoptosis and reduce the regenerative capacity of muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy is the selective removal of dysfunctional mitochondria by autophagic processes (Pryde et al 2016; Wang et al 2011) that requires tagging of dysfunctional mitochondria so that they can be recognized for disassembly. The selectivity of mitophagy is controlled by the loss of the mitochondrial membrane potential (Δψm) and by several important proteins such as BCL2 interaction myosin/moesin like coiled-coil protein 1 (Beclin1), in conjugation with autophagy-related gene (ATG) family members which support lipidation of microtubule associated protein light chain 3 (LC3)-I to LC3-II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terminal dUTP nick-end labeling (TUNEL) was performed to detect apoptotic nuclei in tissue cross sections, as previously described (32, 74). Briefly, frozen tissue (10 μm thick) cross sections of left ventricle were mounted on charged microscope slides (Fisher Scientific, Pittsburgh, PA), air dried, and incubated overnight at 4°C with mouse anti-heavy chain cardiac myosin antibody (no.…”
Section: Methodsmentioning
confidence: 99%